Analisis Pengujian Konsumsi Bahan Bakar dan Performa pada Sepeda Motor Honda 110 cc Menggunakan Knalpot AHLM (Adaptive High-Performance, Low-Pollution Muffler) - Fayisa, Fadhil; Roziqin, Ahmad; Naryanto, Rizqi Fitri; Septiyanto, Angga; Maulana, Sonika; Rohman, Shohihatur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Motor vehicle emissions and energy efficiency are key concerns in developing environmentally friendly automotive technologies, particularly for small-capacity motorcycles, which remain the dominant mode of transportation in Indonesia. This study aims to analyze the effect of using the AHLM (Adaptive High-Performance, Low-Pollution Muffler) on fuel consumption and engine performance in a Honda 110 cc motorcycle. The research employed a comparative experimental method using three types of exhaust systems: standard, free flow, and AHLM. Tests were conducted using an engine dynamometer to measure torque and power, and a fuel consumption tester to record the time required to consume 10 ml (0.0074 kg) of fuel, calculated using the conversion formula m = (V_ml / 1000) × ρ, at three engine speeds: 1500 rpm, 2500 rpm, and 3500 rpm. The results show that the free flow exhaust produced the highest torque and power, at 10.9 Nm and 11.7 HP at 9000 rpm, respectively, but with higher fuel consumption. Conversely, the AHLM exhaust demonstrated better fuel efficiency, with consumption rates of 0.083 kg/h at 1500 rpm, 0.317 kg/h at 2500 rpm, and 0.416 kg/h at 3500 rpm, closely matching the efficiency of the standard exhaust. Although its peak power was slightly lower, the AHLM maintained stable torque and efficient combustion across all engine speeds. In conclusion, the AHLM exhaust system provides an optimal balance between performance and energy efficiency, offering potential as an adaptive exhaust technology that is both effective and environmentally friendly for small-capacity motorcycles.